Clinical utility of endorectal MRI‐guided prostate biopsy: Preliminary experience. Issue 2 (31st October 2013) - Jung, Adam J.; Westphalen, Antonio C.; Kurhanewicz, John; Wang, Zhen J.; Carroll, Peter R.; Simko, Jeffry P.; Coakley, Fergus V.
<x xml:space="preserve">Abstract</x> Purpose To investigate the potential clinical utility of endorectal MRI‐guided biopsy in patients with known or suspected prostate cancer. Materials and Methods We prospectively recruited 24 men with known or suspected prostate cancer in whom MRI‐guided biopsy was clinically requested after multiparametric endorectal MRI showed one or more appropriate targets. One to six 18‐gauge biopsy cores were obtained from each patient. Transrectal ultrasound guided biopsy results and post MRI‐guided biopsy complications were also recorded. Results MRI‐guided biopsy was positive in 5 of 7 patients with suspected prostate cancer (including 2 of 4 with prior negative ultrasound‐guided biopsies), in 8 of 12 with known untreated prostate cancer (including 5 where MRI‐guided biopsy demonstrated a higher Gleason score than ultrasound guided biopsy results), and in 3 of 5 with treated cancer. MRI‐guided biopsies had a significantly higher maximum percentage of cancer in positive cores when compared with ultrasound guided biopsy (mean of 37 ± 8% versus 13 ± 4%; P = 0.01). No serious postbiopsy complications occurred. Conclusion Our preliminary experience suggests endorectal MRI‐guided biopsy may safely contribute to the management of patients with known or suspected prostate cancer by making a new diagnosis of malignancy, upgrading previously diagnosed disease, or diagnosing local recurrence. J. Magn. Reson. Imaging 2014;40:314–323. © 2013 Wiley Periodicals, Inc.